Prosedur Penanganan Kedatangan dan Keberangkatan Kapal Ekspor Bermuatan Curah Cair pada PT. Tarunacipta Kencana Cabang Tarahan Lampung - Rio Pranata Hutahaean; Suratni Ginting; Masringgit Marwiyah Nst (Jurnal Riset dan Inovasi Manajemen, 2024)
Writing this paper or research paper has the aim and objective of knowing the Procedure for Handling the Arrival and Departure of Export Ships Loaded with Liquid Bulk at PT. Tarahan Cipta Kencana Branch, Lampung Branch. The methods applied are the literature method or (library research) as well as the field inspection method (field research) by describing the Arrival and Departure Handling Procedures for Export Vessels Containing Liquid Bulk Cargo at PT. Tarahan Cipta Kencana Branch, Lampung Branch. In this paper we have explained the obstacles faced, including the cargo not being ready from the shipper and the cargo analysis results not yet being published from the customs and excise agency. There are things that can be done to achieve the goal so that the ship is not hindered in the ship loading process and there are no delays in the ship's departure. So that the ship agency service process can run smoothly, precisely and quickly, PT. Tarunabuat Kencana must pay attention to and prepare all the facilities and infrastructure needed in the ship service process.